2019
DOI: 10.1002/slct.201901379
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐Selective Synthesis of Tetrazole‐Containing Cyclopentenyl Phosphanylidene Dicarboxylates

Abstract: A chemo-selective clean reaction between triphenylphosphine (TPP) and dialkyl acetylenedicarboxylates (DAAD) in the presence of synthesized alkyl 3-phenyl-2-(1H-tetrazol-5-yl)acrylates for generation of the 3-alkyl 1-alkyl 4-oxo-2-phenyl-3-(1Htetrazol-5-yl)-5-(triphenyl-λ 5 -phosphanylidene)cyclopent-1-ene-1,3-dicarboxylates is described. 2 3 4 5 6 7 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In our previous study, we observed that the vinyl phosphonium zwitterionic intermediate (A) reacted with the conjugated C-C double bond instead of the NH of tetrazole, and the reaction proceeded via a Michael addition to produce the final product 8 (Fig. 6) 30 . However, in the current study, neither the, NH of tetrazole nor the conjugated C-C double bond have any reaction with the vinyl phosphonium zwitterion.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In our previous study, we observed that the vinyl phosphonium zwitterionic intermediate (A) reacted with the conjugated C-C double bond instead of the NH of tetrazole, and the reaction proceeded via a Michael addition to produce the final product 8 (Fig. 6) 30 . However, in the current study, neither the, NH of tetrazole nor the conjugated C-C double bond have any reaction with the vinyl phosphonium zwitterion.…”
mentioning
confidence: 98%
“…1). Herein, according to our investigations [27][28][29][30] , due to the importance of organophosphorus compounds and isatin cores, we describe the synthesis of functionalized 2-oxoindoline-3-ylidene containing novel organophosphorus compounds. Therefore, we have performed a facile one-pot reaction between 2-oxoindoline-3-ylidene derivatives and triphenyphosphine or triphenyl phosphite in the presence of acetylenic esters.…”
mentioning
confidence: 99%
See 1 more Smart Citation